2011
DOI: 10.1016/j.apal.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds on ideals in the computably enumerable Turing degrees

Abstract: a b s t r a c tWe study ideals in the computably enumerable Turing degrees, and their upper bounds. Every proper Σ 0 4 ideal in the c.e. Turing degrees has an incomplete upper bound. It follows that there is no Σ 0 4 prime ideal in the c.e. Turing degrees. This answers a question of Calhoun (1993) [2]. Every proper Σ 0 3 ideal in the c.e. Turing degrees has a low 2 upper bound.Furthermore, the partial order of Σ 0 3 ideals under inclusion is dense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Yates showed that each Σ 0 3 ideal of R T is uniformly generated. In Barmpalias and Nies (2011), it is shown that K forms a Σ 0 3 ideal of R T , and K has a low 2 c.e. upper bound.…”
Section: Upper Boundsmentioning
confidence: 99%
“…Yates showed that each Σ 0 3 ideal of R T is uniformly generated. In Barmpalias and Nies (2011), it is shown that K forms a Σ 0 3 ideal of R T , and K has a low 2 c.e. upper bound.…”
Section: Upper Boundsmentioning
confidence: 99%
“…From the point of view of classical computability theory, the study of the ideal of the K-trivial sequences in the Turing degrees has attracted considerable attention. A number of results about the upper bounds of this ideal where established in [58,23,10], in response to [68,Questions 4.2 and 4.3]. The study of the quotient structure of the c.e.…”
Section: Triviality Notionsmentioning
confidence: 99%
“…This turns out to be a Σ 0 3 ideal, in the sense that the index set of its members is Σ 0 3 . Moreover by [BN11] it has a c.e. upper bound that is strictly below the degree 0 of the halting problem (moreover, by [KS09] it has a low upper bound b, which means that the halting problem relativized to b has degree 0 ).…”
Section: Introductionmentioning
confidence: 99%